Should UK membership exams be held overseas? No. (28th July 2011) - Devakumar, Delan; Mandeville, Kate
Abstract : Graeme Muir and Justin Thacker (doi:10.1136/bmj.d4566 ) believe that UK professional qualifications can help other countries improve training and standards, but Delan Devakumar and Kate Mandeville argue that they lack local relevance